Segurança alimentar no município de Iguatu-CE: uma abordagem a partir dos programas de aquisição de alimentos da agricultura familiar - Batista, Iltânia Maria Vieira (2013)
This study aimed to describe the food security in the municipality of Iguatu, having as object of analysis the development of programs of acquiring food from the family farming and the bond that was built with other programs such as school meals and assistance to people facing social vulnerability, such as Milk Zero Hunger Program, the Community Kitchen and Food Bank in the implementation phase. The methodology consisted of bibliographic and documentary research, in order to describe the evolution of food safety policy in the country, the contribution of the development of programs of food acquisition in ensuring food security and the analysis of the municipality of Iguatu - CE in promoting food security. The results of the research showed significant advances in the food security policy at the national level, based on the Law of Food and Nutritional Security and on the guarantee of the human right to adequate food. Among the governmental programs, the research highlighted the PRONAF and the Food Purchase Program for its specific emphasis at the family farming, given its leading role in the food production and its contribution to the food security. The municipality of Iguatu got inserted in the food security policy, by creating a specific municipal legislation and the necessary institutions for the development of Food and Nutritional Security actions. Acquisition programs of food from family farmers contributed significantly to reach people in social vulnerability and enriched the school lunch menu, with fresh produce, ensuring especially fruits and vegetables. The research concluded that there is commitment at the municipal level to adhere and to implement federal programs that comply with family farming and with people in social vulnerabilities, aiming at food security at the municipality.